K-Pop demon hunters: Visual analysis of costume design in character design to differentiate the eras - Sitorus, Felisa Naomi (Jurnal Desain, 2025)
This study examines how costume design functions as a visual mechanism for temporal differentiation in the animated film K-Pop Demon Hunters. While costume is widely recognized as a semiotic tool in character design, few studies have analyzed its capacity to communicate historical era transitions within animated storytelling. Addressing this gap, the research aims to identify how specific clothing elements—such as silhouette, fabric behavior, color palette, and stylistic detailing—are deployed to signify the narrative’s generational shifts. This study employs a qualitative visual analysis grounded in social semiotic theory by examining costume design as visual signifiers through systematic denotative and connotative interpretation, supported by comparative historical fashion references. The results indicate that each hunter generation is visually anchored to recognizable fashion eras, from early traditional attire to 1920s flapper silhouettes, 1940s wartime utility wear, 1960s mod styles, and contemporary K-Pop aesthetics. Findings further show that costume design not only conveys an era through appearance but also through stylistic choice, where fashion personality reinforces temporal and narrative authenticity. The analysis concludes that costume design serves as a narrative scaffold, enabling viewers to understand chronological progression without verbal exposition. These insights underscore the importance of integrating fashion history and digital costume practices in animation pipelines. Future projects may expand this framework by exploring audience perception studies or cross-cultural interpretations of era-based costume cues.